Standardization of a well-controlled in vivo mouse model of thrombus formation induced by mechanical injury. Issue 141 (May 2016) - Tang, Chaojun; Wang, Yinyan; Lei, Daoxi; Huang, Lu; Wang, Guixue; Chi, Qingjia; Zheng, Yiming; Gachet, Christian; Mangin, Pierre H.; Zhu, Li
Abstract: Objective: Vascular plug formation by mechanical injury that exposes abundant extracellular matrix is an ideal model to mimic thrombus formation. The objective of this study was to standardize our previously established in vivo mouse model of thrombus formation induced by mechanical injury. Results: The mechanical injury was exerted by pinching the abdominal aorta with hemostatic forceps for either 15 (moderate injury) or 60 (severe injury) seconds. Thrombus formation was monitored for 20 min in real time using a fluorescent microscope coupled to a CCD camera. In the moderate injury, thrombus formation peaked at approximately 1 min after injury and resolved within 3 min, with the mean AUC (area under the curve) of 165.2 ± 17.29 mm 2, whereas a larger thrombus was observed upon the severe injury, with the mean AUC of 600.5 ± 37.77 mm 2 . Using scanning electron microscopy and HE staining, a complete deformation of the endothelium in the moderate injury model and the exposure of the media in the severe injury model were observed. The model was also evaluate for its application on the effects of antithrombotic drugs targeting GP IIb–IIIa (eptifibatide), ADP receptor P2Y1 (MRS2500) and P2Y12 (clopidogrel), and thrombin (hirudin) on thrombus formation. Conclusions: We have improved a vascular injury model with optimal reproducibility and feasibility that allows evaluating the effect of anti-thrombotic drugs on thrombus formation in vivo. Highlights: This study aimed to standardize our previously established mouse model of thrombus formation induced by mechanical injury. We improved it by applying two degrees of calibrated pinching in order to induce two defined degrees of vessel injury severity. We analyzed the real-time thrombus formation, pathological changes of the vessel wall, and its applicability for anti-thrombotic evaluation. This model generates a large scope of vessel injury, allowing relatively flexible applications with reproducibility and feasibility.